2001
DOI: 10.1046/j.1442-200x.2001.01352.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density in children with cerebral palsy

Abstract: The present study showed that BMD was decreased in all children with CP, but to a greater extent in non-ambulant children with CP, and immobilization is the major effective factor on bone mineralization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
24
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 12 publications
5
24
0
Order By: Relevance
“…In this study, all values of bone markers in children with CP were within normal limits. These findings were consistent with most previous studies 8,23 . Previous studies demonstrated that serum calcium and phosphate levels were significantly higher in children with CP than in the control group, 23 although the serum calcium and phosphate levels were within normal limits 23 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, all values of bone markers in children with CP were within normal limits. These findings were consistent with most previous studies 8,23 . Previous studies demonstrated that serum calcium and phosphate levels were significantly higher in children with CP than in the control group, 23 although the serum calcium and phosphate levels were within normal limits 23 .…”
Section: Discussionsupporting
confidence: 93%
“…These findings were consistent with most previous studies 8,23 . Previous studies demonstrated that serum calcium and phosphate levels were significantly higher in children with CP than in the control group, 23 although the serum calcium and phosphate levels were within normal limits 23 . A significant elevation of phosphate levels in children with CP may imply higher bone resorption 23 .…”
Section: Discussionsupporting
confidence: 91%
“…The observed normocalciuria in most GSF supports previous studies that concluded that the hypercalciuria secondary to immobility is likely a transient phenomenon, with urine calcium levels returning to normal after two weeks [1,2]. These data suggest that neither immobility nor hypercalciuria in and of themselves are the major risk factor in the nephrolithiasis seen in GSF.…”
Section: Discussionsupporting
confidence: 85%
“…[8][9][10][11] In a previous cross sectional study 12 we reported that the degree of reduction in calcaneal broadband ultrasound attenuation (related to BMD and bone structure) and vertebral volumetric trabecular BMD were associated with the degree of immobility and non-weight bearing of the subjects. Nutritional factors that contribute to low BMD in these children with CP include low intake of calcium due to feeding and swallowing difficulties 13 14 and increased catabolism of vitamin D in those treated with anticonvulsants.…”
mentioning
confidence: 94%